Serological and molecular characteristics of pathogenic Leptospira in rodent populations in Fujian Province, China, 2018–2020 - Guoying Xu; Haiyan Qiu; Weijun Liu; Xiugao Jiang; Yung-Fu Chang; Jiaxiong Wang; Zhenpeng Li; Yongzhang Zhu; Cuicai Zhang; Fangzhen Xiao (BMC Microbiology, 2022)
Abstract Background Leptospirosis is a significant emerging infectious disease worldwide. Rodents are considered to be the most critical hosts of Leptospira spp. Fujian Province is a region highly endemic for leptospirosis in China. However, the genetic diversity of leptospires circulating among rodents in Fujian is limited. Results The carrier status of rodents for Leptospira spp. was investigated by culture and serological detection in Fujian during 2018–2020. A total of 710 rodents, including 11 species, were trapped, with Rattus losea being the dominant trapped species (50.56%). Fourteen pathogenic Leptospira strains were obtained. Seven L. borgpetersenii serogroup Javanica strains belonging to ST143, 4 L. interrogans serogroup Icterohaemorrhagiae strains belonging to ST1 and ST17, 2 L. interrogans serogroup Bataviae strains belonging to ST96 and ST333, and 1 L. interrogans serogroup Pyrogenes strains belonging to ST332 were identified using 16S rDNA gene sequencing, microscopic agglutination test (MAT) and Multilocus sequence typing (MLST). L. borgpetersenii serogroup Javanica belonging to ST143 was the dominant type (50.00%). A total of 387 rodent serum samples were tested by MAT. Serum were considered positive for seroreactivity at a titer ≥ 1:160 against at least one serovar. A total of 90 (23.26%) serum samples tested positive, and four serogroups were identified, with Javanica being the dominant serogroup (87.78%), which was similar to the dominant serogroup isolated from rodents. This study demonstrates a high prevalence of leptospirosis in rodents and public health education among high-risk workers is highly recommended. Conclusions R. losea was the dominant trapped rodent, and L. borgpetersenii serogroup Javanica ST143 was widely distributed among rodents in Fujian from 2018 to 2020. Despite the low number of isolates obtained from rodents, this study suggests that continuous epidemiological surveillance of the aetiological characteristics of pathogenic Leptospira in wild animal reservoirs may help reduce the possible risk of disease transmission.